1976
DOI: 10.1177/24.1.943439
|View full text |Cite
|
Sign up to set email alerts
|

Spectral studies on 33258 Hoechst and related bisbenzimidazole dyes useful for fluorescent detection of deoxyribonucleic acid synthesis.

Abstract: Absorption, fluroescence and circular dichroism measrements on 33258 Hoechst-deoxyribonucleic acid (DNA) complexes are consistent with the existence of two types of dye-binding interactions. One type, which persists at elevated solution ionic strength, is highly specific for adenine-thymine-rich DNA. Dye bound under this condition exhibits efficient fluorescence and strong optical activity. A less specific, largely electrostatic interaction is associated with less intense fluorescence and weaker optical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
166
2
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 342 publications
(172 citation statements)
references
References 24 publications
3
166
2
1
Order By: Relevance
“…Incubation of cells in the presence of BrdUrd results in incorporation of this precursor into DNA resulting in altered staining properties of this biopolymer (11)(12)(13)(14)(15). In a previous paper we reported that after differential staining of DNA versus RNA with AO, proliferating human lymphocytes exposed to BrdUrd for one generation had a 40% decrease in DNase-sensitive green fluorescence when compared with noncycling lymphocytes or cycling cells incubated in the absence of this precursor (4).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Incubation of cells in the presence of BrdUrd results in incorporation of this precursor into DNA resulting in altered staining properties of this biopolymer (11)(12)(13)(14)(15). In a previous paper we reported that after differential staining of DNA versus RNA with AO, proliferating human lymphocytes exposed to BrdUrd for one generation had a 40% decrease in DNase-sensitive green fluorescence when compared with noncycling lymphocytes or cycling cells incubated in the absence of this precursor (4).…”
Section: Discussionmentioning
confidence: 99%
“…The present technique, as well as other techniques of BrdUrd detection, based on suppression or enhancement of DNA stainability with various fluorochromes (1,4, [11][12][13][14][15]17) suffer in general from low sensitivity. In this respect they are inferior to immunochemical approach (9) which detects as little as 4% of the replicated genome and, therefore, may be applied after short (30 min) pulse of BrdUrd.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations